Evaluation of Different Preservation and Storage Methods for Malassezia spp. - Crespo, M. J. (American Society for Microbiology, 2000)
Freezing at −80°C, lyophilization, preservation in distilled water, and storage in different culture media were performed in order to find a suitable method that allowed a prolonged storage of Malassezia spp. Freezing at −80°C was the only method successful at maintaining all species.